Prevalence survey of healthcare associated infections in a large teaching hospital. (13th November 2019) - Castellani, F; Barbato, D; Angelozzi, A; Isonne, C; Baccolini, V; Migliara, G; Marzuillo, C; De Vito, C; De Giusti, M; Villari, P
Abstract: Background: Healthcare Associated Infection (HAI) is the most frequent adverse event in healthcare settings. It is associated with an increased mortality and antimicrobial resistance, prolonged hospital stays and consistent financial loss for the healthcare systems. The objective of this study was to estimate the burden of HAIs and antimicrobial use in the Teaching Hospital Policlinico Umberto I (THPUI) of Rome to identify the most critical areas for interventions. Methods: Data were collected according to the most recent ECDC Point Prevalence Survey protocol in November 2018. Descriptive statistics for all variables were calculated. Univariate analysis was used to assess possible associations between variables and HAIs. Variables with a significance level of p < 0.25 were included in a multiple logistic regression model. Results: A total of 799 patients were included in the analysis; of these, 13.3% presented at least one HAI. Bloodstream infection was the most common, accounting for 30.9% of the total infections. Globally, 125 microorganisms were isolated, with Enterobacteriaceae being the most frequent (32%). At the time of the survey, 49.1% patients were receiving antimicrobial therapy. The multivariate analysis showed a significant association between HAI and use of medical devices (OR = 34.30, IC95%:3.69-318.66), length of stay (OR = 1.01, IC95%:1.00-1.02) and the exposure to prophylactic antimicrobial therapy (OR = 0.23, IC95%:0.11 -0.47). Conclusions: Our HAI prevalence was higher than the European standard (6.7%). This highlights the need of implementing targeted measures to prevent and control HAIs and a continuous monitoring to evaluate the effectiveness of such interventions. Another step could be the elaboration of a survey to investigate the knowledge, attitudes and practices of healthcare workers towards HAIs in order to raise awareness, enhance surveillance strategies and promote educational interventions. Key messages: It was important to quantify the burden of HAIs in the THPUI in order to identify the main areas for interventions. Several activities will be implemented to contain this problem.